Optimization of Inverted All-Inorganic CsPbI3 and CsPbI2Br Perovskite Solar Cells by SCAPS-1D Simulation - Pinzón Rueda, Carlos Alberto (2022)
Perovskite solar cells (PSCs) have substantially increased their power conversion efficiency(PCE) to more than 25% in recent years. However, the instability of these devices is still astrong obstacle for their commercial applications. Recently, all-inorganic PSCs based on CsPbI3 andCsPbI2Br as the perovskite layer have shown enhanced long-term stability, which makes them potentialcandidates for commercialization. Currently, all-inorganic PSCs with inverted p-i-n configurationhave not yet reached the high efficiency achieved in the normal n-i-p structure. However, theinverted p-i-n architecture has recently drawn attention of researchers because it is more suitable toprepare tandem solar cells. In this work, a theoretical study of inverted p-i-n all-inorganic PSCsbased on CsPbI3 and CsPbI2Br as the perovskite layer was carried out using SCAPS-1D software.The performance of different architectures of PSC was examined and compared by means of numericalsimulations using various inorganic materials as the hole transport layer (HTL) and theelectron transport layer (ETL). The results reveal that CuI and ZnO are the most suitable as HTLand ETL, respectively. In addition, the performance of the devices was significantly improved byoptimizing the hole mobility in CuI as well as the thickness, doping density, and defect density inthe absorber layer. Maximum efficiencies of 26.5% and 20.6% were obtained under optimized conditionsfor the inverted all-inorganic CsPbI3- and CsPbI2Br-based PSCs, respectively. These resultsindicate that further improvements in the performance of such devices are still possible.